Parents' views on toilet training (TT): A quantitative study to identify the beliefs and attitudes of parents concerning TT. (June 2015) - van Nunen, Karolien; Kaerts, Nore; Wyndaele, Jean-Jacques; Vermandel, Alexandra; Hal, Guido Van
Background: In recent years, the age at which parents start and finish toilet training (TT) their children has increased. To cope with the problems caused by this later completion, it is essential to identify the beliefs and attitudes of the parents. Methods: Two thousand questionnaires were distributed to parents of children aged 30 to 36 months, attending 50 randomly selected schools in Antwerp, Belgium. Results: Too many children are toilet trained after the minimum school age of 30 months. Most parents are not aware of the possible negative consequences this can entail. Mothers with a paid occupation think more often that children should be toilet trained before the age of 30 months, and the higher the mother's educational level, the more likely she will send her child to school toilet trained. More of single parents think that children who are not yet toilet trained should be allowed to go to school and more often send their not fully toilet-trained children to school. Conclusion: Parents should be better informed about the possible negative consequences of a later completion of TT. Single parents, more than other parents, should be assisted in the TT process and offered more support.